Quantitative Risk Assessment of Hydrogen Refueling Station in Cheonan City of South Korea - Jeon, Bo Il; Kim, Shinji; Yoon, Yeo Song; Jung, Seungho (Energies, 2023)
The average temperature of the Earth has risen due to the accumulation of greenhouse gases emitted from the usage of fossil fuels. The consequential climate changes have caused various problems, fueling the growing demand for environmentally friendly energy sources that can replace fossil fuels. Batteries and hydrogen have thus been utilized as substitute energy sources for automobiles to reduce fossil fuel consumption. Consequently, the number of hydrogen refueling stations is increasing due to an increase in the number of hydrogen-powered vehicles. However, several incidents have been reported in the United States of America and Japan where hydrogen refueling stations have been operating for a long time. A risk assessment of hydrogen refueling stations operating in urban areas was performed in this study by calculating the risk effect range using a process hazard analysis tool (PHAST) v8.7 from DNV-GL and a hydrogen risk assessment model (HyRAM) from Sandia National Laboratories (SNL). The societal risk was assessed through a probit model based on the calculation results. The assessment results showed that the risk caused by jet fire and overpressure in an incident is lower than the ‘as low as reasonably practicable’ (ALARP) level.
Keywords: Energy source; Hazard analysis tools; Hydrogen refueling stations; Hydrogen risk assessment model; Hydrogen risks; Probit models; Process hazard analyse tool; Process hazards analysis; Quantitative risk assessment; Risk assessment - modelling; hydrogen refueling station; HyRAM; PHAST; probit model; quantitative risk assessment